SOSIALISASI HUKUM BAGI MASYARAKAT MENGENAI PEMENUHAN KEWAJIBAN KREDIT SELAMA MASA PANDEMI COVID-19 - D.Y. Utami, P.; G.P. Yustiawan, D.; A.S. Utari, A.; T.L. Hadjon, E. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
During the COVID-19 pandemic, there were legal problems experienced by the public regarding ignorance of the existence of a credit restructuring program from the government to deal with non-performing loans during the COVID-19 pandemic and a lack of understanding regarding the relative nature of force majeure from the COVID-19 pandemic which did not eliminate credit obligations, but only suspended through relief on credit restructuring efforts. The activity is located in Satra Village, Klungkung Regency. This community service activity aims to provide understanding for people of Satra Village who have non performing loan credit during the COVID-19 pandemic. Considering that the COVID-19 pandemic has greatly affected the economic level of the community, this activity also aims to provide an understanding for the people of Satra Village, that during the COVID-19 pandemic the banks will not immediately execute collateral objects when credit problems occur, but the community can be given payment relief through efforts credit restructuring.The implementation of service activities is carried out by providing in-depth socialization, discussion and question and answer so that the goals of community service activities can be achieved very well. The results of this activity indicate that the activity was carried out very effectively, as evidenced by the enthusiasm of the respondents who are the general public, village administrators and BUMDES administrators in Satra Village in listening to the presentation of the service team. Keywords: Socialization, non performing loan, restructurization, COVID-19.